PHILOSOPHICAL AND ARTISTIC ANALYSIS OF "BHAID BHARI AWAZ" BY IRFAN SADDIQUI - Riffat Kabir Khan; Dr. Rukhsana Bibi (Zaban-o-Adab, 2023)
Drama that is transmitted through radio listened through ears and exhibited through high, low pitches of sound is Radio Drama. Irfan Sadiqui’s book "Bhaid Bhari Awaz" encapsulates moral and social aspects of society, through a mysterious sound. It fabricates deepest emotions and darkest realities of human development along with time. It also portrays love for nation and culture. All the stories are crafted with human emotions with a touch of fantasy, melancholy, lurch, pride, exile, redemption and salvation. Irfan Siddiqui is one of the prominent radio dramatists who emerged in the seventies. He brought to light new trends in his plays. The themes of his plays adopt an attitude of resistance against oppression, exploitation, economic inequalities, chaos and self-indulgence in our society.